Pemanfatan Ekstrak Jamur Tiram (Pleurotus spp.) pada Penyimpanan Daging Ayam pada Suhu Ruang (26oC) - Saskiawan, Iwan; Sukarminah, Een; Lanti, Indira; Marta, Herlina; Nabila, Putri (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTRecently, food preservation especially for meat is becoming one of the subjects of food technology that is still developed. Organic acids is commonly used for food preservative. Meat is easily destroyed mainly by Staphylococcus aureus and Escherichia coli. Oyster Mushroom (Pleurotus spp.), well known as an edible mushrooms is one of the food resources that have antimicrobial activity. The application of oyster mushroom extracts in chicken meat is done using extract concentrations of 0%, 12.5%, 18.75%, 25%, 31.25% and 37.5% where 12,5% is the MIC to inhibit E. coli and S. aureus. The results showed that the application of brown oyster mushroom extracts with concentration of 31.25% can mantain freshness of chicken meat for 12 hours of storage at room temperature (26oC) with the total number of microbes of 8.6 x 105 cfu/g, the total number of E. coli of 0.3 x 101 cfu/g, the total number of S. aureus of 7.7 x 101 cfu/g. It was appropriate with Indonesian National Standard ( SNI 3924:2009). It required the condition such as no decomposition, pH 5.53, color organoleptic value of 3.42 (fair to good) and texture organoleptic value of 3.53 (fair to good).Keywords : oyster mushroom extract, antimicrobial, chicken meat preserving